(untitled) (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
This article discusses the importance of studying the dramatic works of the People’s Poet of Uzbekistan, the renowned playwright Usmon Azim, in comparison with their stage interpretations.